The use of Curcuma longa extract to control Edwardsiella tarda infection on Clarias sp. - Wahjuningrum, Dinamella; Ikhsan, Muharram Nur; Sukenda, ,; Evan, Yan (Jurnal Akuakultur Indonesia, 2014)
ABSTRACT  Target production of catfish in aquaculture can be reached by suppressing the pathogenic bacterial infection. Previous works had shown that turmeric Curcuma longa has antibacterial activity. The objectives of this research were to determine the best method of extraction and to evaluate the efficacy of turmeric extract as feed additive to control Edwardsiella tarda disease in catfish culture. Briefly, the objective was achieved through in vitro assay based on inhibition ability of extraction method against E. tarda, while the following objective was obtained through in vivo assay based on their survival during challenge test either as preventive or curative measurement. A complete randomized design with three replications was used for each assay. Furthermore, challenge test was done by mean intraperitoneal injection at concentration 106 cfu/mL of E. tarda (LD50). The results showed that 15 minutes decoction method allowed the best inhibition with diameter 7.42 mm of clear zone and then curative measurement using turmeric extract could be the best application against E. tarda since it gave 86.67% of survival. Clinical signs such as swelling, hemoraghic, body ulcer, gastroentritis and gaseous captivity were observed on challenged fish. However, there were no significant different among treatments for specific growth, body weight, and absolute length parameters.  Keywords: Edwardsiella tarda, extraction, turmeric, catfish, inhibition zone  ABSTRAK Peningkatan produksi ikan lele dapat dicapai melalui pencegahan infeksi penyakit bakterial. Hasil beberapa penelitian membuktikan bahwa kunyit Curcuma longa terbukti memiliki zat aktif yang bersifat antibakteri. Penelitian ini bertujuan untuk mencari metode ekstraksi terbaik dan mengevaluasi efektivitas penambahan ekstrak kunyit pada pakan untuk pengendalian patogen Edwardsiella tarda pada ikan lele. Metoda ekstraksi kunyit diuji secara in vitro dengan metoda zona hambat, sedangkan efikasi diuji secara in vivo melalui perlakuan pencegahan dan pengobatan. Penelitian didesain dalam rancangan acak lengkap dengan tiga ulangan. Efikasi ekstrak kunyit diketahui dari nilai sintasan ikan lele hasil uji tantang E. Tarda melalui injeksi peritoneal dengan dosis 106 cfu/ mL (LD50). Hasil uji in vitro menunjukkan bahwa metode dekoksi selama 15 menit memberikan zona hambat terbaik yaitu sebesar 7,42 mm. Hasil uji in vivo menunjukkan bahwa ekstrak kunyit sebagai tindak pengobatan memberikan nilai sintasan terbaik, yaitu sebesar 86,67%. Ikan lele yang diuji tantang menunjukkan gejala klinis berupa pembengkakan, luka, gastroentritis, dan gas pada perut. Tidak terdapat perbedaan nyata di antara perlakuan untuk parameter laju pertumbuhan harian, bobot harian, dan pertumbuhan panjang mutlak. Kata kunci: Edwardsiella tarda, ekstraksi, kunyit, ikan lele, zona hambat